2015
DOI: 10.1091/mbc.e15-07-0469
|View full text |Cite
|
Sign up to set email alerts
|

Hcm1 integrates signals from Cdk1 and calcineurin to control cell proliferation

Abstract: The transcription factor Hcm1 is a key regulator of chromosome segregation and genome stability. The phosphatase calcineurin directly inactivates Hcm1 in response to environmental stress, which inhibits proliferation. Hcm1 functions as a rheostat, whose phosphorylation state affects the rate of proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 47 publications
(65 reference statements)
6
29
2
Order By: Relevance
“…These results are in agreement with a report that phosphorylation of the N-terminal region of Hcm1 promotes its degradation (16). Our MS analysis revealed many in vivo Hcm1 phosphorylation sites at different positions outside the N-terminal region, which includes some of the C-terminal phosphorylation sites suggested to regulate Hcm1 function (16,47). The positive regulatory phosphorylation of those sites is thought to be promoted during the cell cycle in a CDK-dependent manner (16,39).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with a report that phosphorylation of the N-terminal region of Hcm1 promotes its degradation (16). Our MS analysis revealed many in vivo Hcm1 phosphorylation sites at different positions outside the N-terminal region, which includes some of the C-terminal phosphorylation sites suggested to regulate Hcm1 function (16,47). The positive regulatory phosphorylation of those sites is thought to be promoted during the cell cycle in a CDK-dependent manner (16,39).…”
Section: Discussionsupporting
confidence: 92%
“…Arsenault et al reported that environmental stresses dephosphorylate C-terminal phosphorylation sites through the Cnb1 calcium-activated phosphatase, thereby negatively regulating Hcm1 function, and suggested Hcm1 as a rheostat that controls cell proliferation (47). Our analyses indicated that N-terminal phosphorylation sites influence the cell wall stress response by negatively regulating Hcm1 protein level at the cell wall integrity checkpoint, suggesting a role for Hcm1 as a brake.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…One mechanism by which CN could enforce a cell cycle arrest is by downregulating expression of genes that drive the cell cycle forward. The S-phase TF Hcm1 is an established target of CN (Arsenault et al, 2015); however, an Hcm1 mutant that cannot interact with CN had no effect on CN-mediated response to stress (hcm1DP, Figures 1A and S1A). To determine if CN impacts the activities of other cell cycleregulatory TFs, RNA-seq was performed on samples from CaCl2 time course experiments and the average change in gene expression of targets of each TF was compared between control and FK506-treated cells.…”
Section: Cn Downregulates Multiple Clusters Of Cell Cycle Genesmentioning
confidence: 99%
“…A few cell cycle regulators have also been identified as CN targets, suggesting that CN may help coordinate the stress response with cell cycle arrest (Goldman et al, 2014;Mizunuma et al, 2001). Inactivation of the S-phase specific transcriptional activator Hcm1 by CN leads to decreased expression of its target genes, which include TFs that act at a later stage in the cell cycle (Arsenault et al, 2015). However, it is not known if CN impairs cell cycle-regulated gene expression solely through inactivation of Hcm1, or if CN regulates the TF network through additional mechanisms.…”
Section: Introductionmentioning
confidence: 99%